2021
DOI: 10.1016/j.appet.2021.105192
|View full text |Cite
|
Sign up to set email alerts
|

‘Eating well’ in Pacific Islands countries and territories: A qualitative and normative approach to food cultures in New Caledonia

Abstract: In recent decades, the food cultures of the Pacific populations have undergone a profound transition, particularly because the increasing trade exchanges with Western countries have facilitated access to a wide range of processed foods. Essentially, a new normative model of eating is now taking the place of the traditional models. The aims of this qualitative study were to explore what 'eating well', 'good food' and 'bad food' now mean in the New Caledonian family context and, more broadly, to categorise the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…One pervasive attitude was that healthy eating has negative financial impacts primarily due to the price of substituting healthier foods for unhealthy foods. Price has previously been identified as a major barrier to healthy eating in the US [ 6 , 8 , 12 , 13 , 14 ] and outside of the US [ 18 , 19 , 20 , 21 , 22 ]. In this study, participants shopped at discount stores or outside of their local community (i.e., outshopping) to obtain better prices and quality foods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One pervasive attitude was that healthy eating has negative financial impacts primarily due to the price of substituting healthier foods for unhealthy foods. Price has previously been identified as a major barrier to healthy eating in the US [ 6 , 8 , 12 , 13 , 14 ] and outside of the US [ 18 , 19 , 20 , 21 , 22 ]. In this study, participants shopped at discount stores or outside of their local community (i.e., outshopping) to obtain better prices and quality foods.…”
Section: Discussionmentioning
confidence: 99%
“…Residents of rural and remote environments in Canada, Uganda, Australia, and the Pacific Islands countries reported that EDNP foods are more available due to increased trade. Consequently, EDNP foods are considered a barrier to the consumption of healthy traditional foods in their respective cultures [ 18 , 19 , 20 , 21 , 22 ]. Healthy eating promotions in these remote locations encourage the intake of traditional healthy foods shared with family and friends for the prevention of obesity and chronic disease [ 18 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…105 Purchasing a candy bar for one's child or eating out in a fast food restaurant can provide relief from the stresses of low-wage work and poverty, or a rare moment of tranquility when tired working parents can enjoy a meal with their family. [106][107][108] For those experiencing homelessness, UPF consumption is driven by practical considerations such as lacking a space to cook or store food and limited resources to spend on food. However, UPFs can also offer a chance to exert control in context of the limited privacy and limited food choices in shelters.…”
Section: Peoplementioning
confidence: 99%
“…109 Among adolescents, the appeal of UPF can be driven by the social interaction and independence it confers, while adolescents who value home-cooked meals with their families report finding UPF less appealing. 63,100,108 Other research examines the ways fast food establishments have been deliberately designed to function as 'third places,' i.e., spaces that are neither fully public nor private where people can socialize, found to be especially important for older people. 110,111 On the other hand, for some adults, eating alone facilitates the consumption of UPF, 62 perhaps because it requires less effort than cooking for oneself.…”
Section: Peoplementioning
confidence: 99%